Voice and respiratory outcomes after permanent transoral surgery of bilateral vocal fold paralysis. (1st August 2015) - Nawka, Tadeus; Sittel, Christian; Arens, Christoph; Lang‐Roth, Ruth; Wittekindt, Claus; Hagen, Rudolf; Mueller, Andreas H.; Nasr, Ahmed I.; Guntinas‐Lichius, Orlando; Friedrich, Gerhard; Gugatschka, Markus
Abstract : Objectives/Hypothesis: Bilateral vocal fold paralysis (BVFP) is a rare but life‐threatening condition mostly caused by iatrogenic damage to the peripheral recurrent laryngeal nerve. Endoscopic enlargement techniques have been the standard treatment for decades. However, prospective studies using internationally accepted phoniatric and respiratory evaluation guidelines are rare. Study Design: Prospective observational multicenter study. Methods: Twelve clinical centers screened 61 patients, of whom 36 were eligible according to the study protocol. Subjects were assessed with specific phoniatric and respiratory tests preoperatively and at 1 and 6 months postoperatively. Results: Important respiratory parameters improved significantly 6 months postoperatively (peak expiratory and expiratory flow), confirming that a glottal enlargement effectively reduced the obstruction. Objective parameters dealing with voice quality worsened significantly (maximum phonation time, voice range profile, hoarseness), whereas subjective voice assessment (VHI‐12) did not change significantly. Conclusion: Endoscopic glottal enlargement is an effective method for relieving symptoms of dyspnea due to BVFP. Postoperatively, voice quality objectively worsened; however, this was not perceived by the patients themselves. Laryngostroboscopic findings did not correlate strongly with voice and respiratory outcomes. Level of Evidence: 2b. Laryngoscope, 125:2749–2755, 2015